(3cJGH GddDdhIs - (3Ydj Hf QHf GdWHQj, CHh GdMSf,J (B247 (3g` s
(3ChdgG (B:s
(3Cf GdfYeI RQY GdeMHI hef CMH GdefYe TcQg hEfi hLOJ ai hSYi eYQaI SGFQ cJH YdeGA GdgfO hGdQhe hHGHd ai GdWH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B288s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs